Theoretical Foundation Of Sexual Bribery At Workplace: A Social Legal Perspective - Rahim, Rohani Abdul; Fandi, Fieza Fazlin; Landa, Azizah (Universiti Sains Malaysia, 2016)

(untitled)
Sexual Bribery is most commonly known as quid pro quo sexual harassment that is when a co-worker or supervisor offers an incentive for engaging in sexual relations with them or another employee. The common incentives in exchange for sexual favours includes promotion, wage raise, positive performance review or good recommendation, and special treatment in the workplace. This paper presentation dwells on the theoretical foundation of sexual bribery at workplace. The investigation will examine how conformity to gender norms on masculinity create risk of sexual harassment to women workers particularly. However both sexes are exposed to be sexually harassed via this form of sexual harassment. Power and power relations have substantial influence in organizational theories, place female workers in awkward positions to resist sexual advance. This is because economically they are dependent on their male supervisor as the supervisor coerces the employee's to submit to his/her sexual demands and subjecting her/his employment to that submission. This research paper also sought to explore the manner in which quid pro quo plays a role in effecting sexual advances between male supervisor and female worker. Having employed various peer-reviewed articles, books, dissertations and internet journals on sexual harassment as a methodology, the other aim of this paper was to highlight the detrimental effects of sexual bribery on the psychological aspects of females in the working organization. The findings revealed that victims of sexual bribery suffers the threatened harm or remains submissive to avoid victimization. Understanding the theoretical mechanisms behind this relationship would be helpful to structuring policy initiatives. This study also supported theories that sexual bribery at workplace- harassment of women is not rooted in sexual desire, attraction, or romance. Instead, these are considered behaviours used to penalize gender- non-traditional women, or those who are seen as “weak and deviant” worker by their superior.